TESTING AND RESPONSE TO SYPHILIS IN MOBILITY CONTEXTS: EXPERIENCE REPORT ON THE BR-101 HIGHWAY IN EUNÁPOLIS, BRAZIL - Santos Rocha Novais, Elines; Almeida da Silva, Flaelma; Ferraz Pereira Marinho, Olívia; Dala Bernardina, Igor (Health and Society, 2025)
Syphilis is a sexually transmitted infection (STI) with a high prevalence in Brazil, showing a significant increase in recent years, especially among socially vulnerable groups. Itinerant workers, such as truck drivers and mobile professionals along the BR-101 highway, are at increased risk of exposure due to constant mobility, limited access to regular healthcare services, and unprotected sexual practices. In this context, the present study aims to report the extension-based experience of testing and educational health actions aimed at confronting syphilis in mobile settings, conducted in the municipality of Eunápolis, Bahia. The intervention took place from August to December 2024, in partnership with the Federal Highway Police (PRF) and the Specialized Care Service and Testing and Counseling Center (SAE/CTA), involving 32 participants, mostly men, of mixed race and in productive age. Rapid tests were performed exclusively by qualified SAE/CTA professionals as part of their institutional duties. The students involved in the extension project did not conduct any clinical procedures; their role was limited to supervised observation and analysis of anonymized data previously authorized by the partner technical team. This experience report complies fully with the ethical principles established by Resolution CNS No. 510/2016, as it did not involve direct intervention or identifiable data collection, and is therefore exempt from mandatory submission to a Research Ethics Committee. No participants tested positive for syphilis, although one reported having recently undergone treatment for the disease. Despite the absence of confirmed cases, the study revealed significant exposure to risk factors related to STI transmission, such as multiple sexual partners and lack of condom use. The findings also highlight the high acceptance of rapid testing, the low perception of risk among users, and the effectiveness of extension activities as strategies for promoting sexual health in contexts marked by mobility and social vulnerabilities.